Road user’s perceptions towards motorcycle safety with regards to conspicuity in Malaysia Road Traffic - Muhamad Syukri Abdul Khalid,; Nor Kamaliana Khamis,; Mohd Radzi Abu Mansor,; Mohd Hafzi Md Isa,; Zulhaidi Mohd Jawi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Motorcycles are the top contributor in road crashes in Malaysia with more than 60% of fatal road crashes involved motorcyclists. Conspicuity issue has been one of the major factors of motorcycle crashes especially when travelling at night in rural road areas. Nevertheless, conspicuity issues also contribute to motorcycle crashes in urban road areas where road and vehicle lightings affect the alertness of other road users towards motorcycle presence in the traffic. This study aims to assess road users’ perception of motorcycle safety levels in terms of its conspicuity, at different riding or driving situations at night in the rural and urban areas. A set of questionnaires was developed with experts’ validation, pilot-tested for its reliability and distributed to road users who commute between Klang Valley and Melaka areas. Preliminary analysis from 78 collected data shows that respondents were able to observe better and be more alert of motorcycle presence in road situations when driving in the urban areas compared to the rural areas. Over 80% believe that wearing bright-coloured attires and helmet can enhance motorcycle’s conspicuity and alertness towards other road users. In addition, more than 80% of the respondents agreed that using reflective tapes on the side body of a motorcycle can improve motorcycle visibility, especially at road junctions. These findings could be used as a future initiative by responsible parties in order to reduce motorcycle conspicuity related crashes in Malaysia.